MODEL KOMUNIKASI MULTIKULTURAL MASYARAKAT JAWA PESISIR DENGAN MADURA DI DESA BUKO - Mahfudlah Fajrie; Muhammad Nashrul Haqqi (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2018)
Each region has a unique society that lies behind the existence of habits, language, communication models, and diverse worldviews. The interaction between two communities that have cultural distinctiveness is a multicultural phenomenon. One area representing the phenomenon is Buko Wedung Village, Demak Regency, where Javanese people as natives interact with Madurese immigrant communities. This study aims to find a multicultural communication model of the coastal communities of Java and Madura with Buko Village. This type of research is included in the field research with an ethnographic approach. Determination of informants is done by purposive sampling technique, while data collection is applied by observation, interviews, and documentation. Data were analyzed by a comparative approach, while the data validation process used triangulation techniques. Based on the results of research and data analysis, it was concluded that the multicultural communication model between the Javanese coastal communities and Madurese communities in Buko Village, Demak Regency, used the Gudykust and Kim model, a communication model that assumed two equal communication between each as a sender and receiver. This shows that cultural differences do not cause multicultural communities on the coast to lose their social relations.